Analisis Kadar Unsur Nitrogen (N) Dan Posforus (P) Dalam Lamun (Enhalus acoroides) Di Wilayah Perairan Pesisir Kabonga Besar Kecamatan Banawa Kabupaten Donggala - Ramadhan, Sofyan; Tiwow, Vanny M. A.; Said, Irwan (Universitas Tadulako, 2016)
The caring of community and local government toward sustainability of seagrass ecosystem has not built properly as well as toward the ecosystem of coral reef and mangrove, as a result, this plant needs attention for its sustainability. One of sea grass’s species which is avalaible abundantly in Banawa district Donggala regency, is enhalus acoroides type. This research aims to know the level of nitrogen dan phosphorus in enhalus acoroides which grow in the bay of Kabonga besar, Banawa district Donggala regency. Determination of nitrogen level used kjeldhal method which consisted of destruction, destilation, titration and phosphorus used wet ash method which continued to use the UV-Vis spectrometry. The result showed that the level of nitrogen in sea grass (enhalus acoroides) type was 1.89 in percentage and phosphorus was 0.413 in percentage.